Elucidating emerging therapeutics: P75 receptor modulation reverts tauopathy associated alterations in synapse‐relevant gene expression signatures: Preclinical small‐molecule drug discovery. (7th December 2020) - Latif‐Hernandez, Amira; Losada, Patricia Moran; Yang, Tao; Tran, Kevin C.; Liu, Harry; Lehallier, Benoit; Massa, Stephen M.; Longo, Frank M.
Abstract: Background: In tauopathy mouse models, activity‐dependent synaptic plasticity, as measured by long‐term potentiation (LTP), is compromised. Treatment of tauopathy mice with LM11A‐31, a small molecule modulator of p75 neurotrophin receptor signaling, normalizes LTP. In the present study, we determined whether activity‐dependent gene expression profiles would be altered in stimulated hippocampus (HC) of tauopathy mice, and if prior in vivo treatment with LM11A‐31 would normalize elements of their transcriptional signature. Method: 6 month‐old wildtype and PS19 (P301S) mice were treated daily by oral gavage for 3 months with vehicle or LM11A‐31. Late‐LTP was used in acute HC slices to induce activity‐dependent changes at synapses. After completion of recordings, a RNA sequencing approach was followed to analyze activity‐dependent gene expression and generate transcriptomic profiles, using cutoffs of q<0.05 and fold change > 1.5. Result: Analyses of the 36, 175 expressed transcripts revealed that samples clustered based on the absence (‐) or presence (+) of LTP. Differential gene expression was found in WT/‐LTP vs WT/+LTP (550 upregulated, 176 downregulated genes); in Tau/‐LTP vs Tau/+LTP (1327 upregulated, 702 downregulated genes) and in Tau/+LM11A‐31/‐LTP vs Tau/+LM11A‐31/+LTP (338 upregulated, 143 downregulated genes). There was strong enrichment in pathways involving genes upregulated by LTP induction in all groups, including NF‐kappa B signaling. In contrast, cytokine activity was enriched within the transcripts that were upregulated with LTP in WT and Tau/+LM11A‐31 but not in the Tau group. Next, we analyzed LTP slices from all groups and found that altered gene expression between WT and Tau mice (996 upregulated and 320 downregulated genes) was changed in Tau/+LM11A‐31 (264 upregulated and 409 downregulated genes). GO, KEGG and Reactome enrichment analyses in WT/+LTP vs Tau/+LTP demonstrated that Tau mice show downregulated genes in neuronal system, calcium signaling, glutamatergic synapse and long‐term potentiation; and upregulated genes in aging, apoptosis and glial cell development pathways. Remarkably, the expression levels of genes from these pathways were largely reverted to WT pattern in Tau mice treated with LM11A‐31. Conclusion: Modulating p75NTR might restore tauopathy‐related alterations in synapse‐relevant gene expression profiles. These findings point to candidate signaling modules for understanding synaptic impairment and therapeutic strategies.